“Unrationality Study Double Entry Bookkeeping” Solusi Pengembangan Persamaan Akuntansi pada Presfektif Pembelajaran, Kasus dan Pemahaman yang Universal - Husni Mubarak (Inovbiz: Jurnal Inovasi Bisnis, 2017)
Abstract: This article investigated about double entry bookkeeping (DEB) on the usage side of the learning process, it is not like the previous accounting experts who repeatedly deeply reviewed DEB. Focus assessment of this article is on the develop use of accounting equations Assets = Liabilities + Equity (A=L+E) which is commonly used for approach to understand accounting in introductory accounting study and courses. Development of this concept is a change in equation A = L + E to become A-L = E for transformation from complexcity of transaction. This accounting equiation (A-E = L or L=A-E) just only the consept is for complex understanding and totality frmawork using part of accoutning consept, but the weakness and limitations this article only use argument, assumtion and basic analisys in define framework modification.